Comments on a nonlinear and nonideal electromechanical damping vibration absorber, Sommerfeld effect and energy transfer - Palacios Felix, Jorge Luis [UNESP]; Balthazar, José Manoel [UNESP] (Springer, 2009)
In this paper, we investigated the effectiveness of the linear electromechanical vibration absorber (LEVA) and a nonlinear electromechanical vibration absorber (NEVA) in the vibration attenuation for nonideal structures (NIS). This electromechanical damping device consists of an electrical system coupled magnetically to a mechanical structure under a nonideal excitation. An analysis of the effects of the parameters of coupling and of nonlinear coefficients with increasing of constant torque of the DC motor is presented.
Keywords: Nonideal system; Electromechanical system; Sommerfeld effect; Damping device